The Effectiveness of Persuasive Communication in Change Management: A Human Resource Management Perspective - Rahmi, R.; Hariani, Swarmilah (Golden Ratio of Mapping Idea and Literature Format, 2023)
The contemporary organizational landscape is characterized by constant change, necessitating effective change management strategies to navigate through uncertainties and sustain success. Persuasive communication emerges as a crucial tool within this context, enabling stakeholders to overcome resistance and mobilize support for organizational transformations. Studies within human resource management (HRM) underscore the pivotal role of persuasive communication in driving change, emphasizing its ability to sway opinions, inspire action, and cultivate shared visions among stakeholders. Key themes include the importance of timing, employee profiles, two-way communication, and message strategies in enhancing change satisfaction and managing public sector change. Persuasive communication goes beyond information dissemination, aiming to create resonance and foster buy-in among diverse audiences by leveraging emotional appeal and crafting compelling narratives. It requires a nuanced understanding of human psychology, communication dynamics, and organizational culture, along with strategic alignment with broader organizational goals and values. In the digital age, where communication is increasingly mediated by digital technologies and social media platforms, HRM professionals must leverage the latest tools and techniques to amplify their persuasive efforts and drive meaningful change amidst information overload and fragmented attention spans. Ultimately, persuasive communication serves as a linchpin for connecting organizational aspirations with individual perspectives, fostering alignment and synergy that propel change initiatives forward.